SOME OPTIONS ABOUT DESIGN STUDIOS OF ARCHITECTURAL EDUCATION - Dizdar, Safiye Irem (European Scientific Journal, ESJ, 2014)
Architecture is a discipline which creates healthy, livable and aesthetic spaces for the users using the opportunities of the natural environment to satisfy the needs and desires of the users within specific criterion. As it is the case in other design based disciplines, importance of theoretical and applied studio courses which bring the student design capability and creativity in architectural education is so remarkable. The most important facts that prepare the student for the profession and design process are the basic studio courses which basic design and space concepts are given. This study examines the working methods of students on a project design course and education process using examples.